PEDAGOGICAL CONDITIONS FOR FORMATION OF READYNESS STUDENTS OF THE FACULTY OF MUSIC AND PEDAGOGICAL USE OF COMPUTER TECHNOLOGIES (Pedagogy of Higher and Secondary Education, 2008)
The article deals with the developing of pedagogical conditions that form the readiness of students of the musical teacher's training departments to computer technologies practical use in musical compositions ’ arrangement.